Question
upstudy study bank question image url

Find \( y^{\prime \prime} \) by implicit differentiation. Simplify where possible. \( x^{2}+3 y^{2}=3 \) Need Help? Read It Watch It SIRMIT ANSWED

Ask by Barrett Bernard. in the United States
Feb 24,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The second derivative of \( y \) with respect to \( x \) is \( \frac{d^2y}{dx^2} = -\frac{3y^{2}+x^{2}}{9y^{3}} \).

Solution

Find the second order derivative with respect to \( x \) for \( x^{2}+3y^{2}=3 \). Find the second derivative by following steps: - step0: Find the second derivative with respect to \(x\): \(x^{2}+3y^{2}=3\) - step1: Rewrite the expression: \(\frac{dy}{dx}=-\frac{x}{3y}\) - step2: Take the derivative: \(\frac{d}{dx}\left(\frac{dy}{dx}\right)=\frac{d}{dx}\left(-\frac{x}{3y}\right)\) - step3: Calculate the derivative: \(\frac{d^2y}{dx^2}=\frac{d}{dx}\left(-\frac{x}{3y}\right)\) - step4: Use differentiation rules: \(\frac{d^2y}{dx^2}=-\frac{\frac{d}{dx}\left(x\right)\times 3y-x\times \frac{d}{dx}\left(3y\right)}{\left(3y\right)^{2}}\) - step5: Calculate the derivative: \(\frac{d^2y}{dx^2}=-\frac{1\times 3y-x\times \frac{d}{dx}\left(3y\right)}{\left(3y\right)^{2}}\) - step6: Calculate the derivative: \(\frac{d^2y}{dx^2}=-\frac{1\times 3y-x\times 3\frac{dy}{dx}}{\left(3y\right)^{2}}\) - step7: Calculate: \(\frac{d^2y}{dx^2}=-\frac{3y-x\times 3\frac{dy}{dx}}{\left(3y\right)^{2}}\) - step8: Calculate: \(\frac{d^2y}{dx^2}=-\frac{3y-3x\frac{dy}{dx}}{\left(3y\right)^{2}}\) - step9: Calculate: \(\frac{d^2y}{dx^2}=-\frac{3y-3x\frac{dy}{dx}}{9y^{2}}\) - step10: Calculate: \(\frac{d^2y}{dx^2}=-\frac{y-x\frac{dy}{dx}}{3y^{2}}\) - step11: Substitute back: \(\frac{d^2y}{dx^2}=-\frac{y-x\left(-\frac{x}{3y}\right)}{3y^{2}}\) - step12: Calculate: \(\frac{d^2y}{dx^2}=-\frac{3y^{2}+x^{2}}{9y^{3}}\) The second derivative of \( y \) with respect to \( x \) is \( \frac{d^2y}{dx^2} = -\frac{3y^{2}+x^{2}}{9y^{3}} \).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Bonus Knowledge

To find \( y^{\prime \prime} \) by implicit differentiation, we start with the equation \( x^{2} + 3y^{2} = 3 \). First, differentiate both sides with respect to \( x \): \[ \frac{d}{dx}(x^{2}) + \frac{d}{dx}(3y^{2}) = \frac{d}{dx}(3). \] This gives us: \[ 2x + 6y \frac{dy}{dx} = 0. \] Now, solve for \( \frac{dy}{dx} \): \[ 6y \frac{dy}{dx} = -2x \implies \frac{dy}{dx} = -\frac{2x}{6y} = -\frac{x}{3y}. \] Next, we need to find \( y^{\prime \prime} \). We differentiate \( \frac{dy}{dx} \): \[ \frac{d^2y}{dx^2} = \frac{d}{dx}\left(-\frac{x}{3y}\right). \] Using the quotient rule gives: \[ \frac{d^2y}{dx^2} = -\frac{(3y)(1) - (-\frac{x}{3y^2})(3 \frac{dy}{dx})}{(3y)^{2}}. \] Substituting \( \frac{dy}{dx} = -\frac{x}{3y} \), we simplify and arrive at: \[ y^{\prime \prime} = \frac{-3y^2 - x \left(-\frac{x}{3y}\right) \cdot 3\left(-\frac{y}{3}\right)}{(3y)^{2}}. \] Continuing to simplify, we combine terms and reduce: \[ y^{\prime \prime} = -\frac{3y^2 + \frac{x^2}{3y}}{9y^2}. \] Thus, after cleaning up the math and combining similar terms, we’ll have an expression for \( y^{\prime \prime} \) based on \( x \) and \( y \). Keep simplifying until you reach a manageable form!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy